Attitudes Towards Workload Vis-À-Vis Time Management Practices of Pub-lic Elementary School Teachers in District II-B Olongapo City - Battad, Arjay Balmes (Future Science / FSH-PH Publications, 2024)
This research investigated a total population of 135 elementary school teachers' attitudes toward workload vis-à-vis their level of time management practices in District IIB, Division of Olongapo City from January to March 2023. The researcher employed a descriptive correlational study using a questionnaire as its main instrument. The weighted mean, Analysis of Variance (ANOVA), and Pearson r Product Moment Correlation Coefficient were used to treat data gathered statistically. In general, the findings indicated a positive teacher’s attitude towards workload. Also, results postulated neutral time management practices among teacher-respondents. Moreover, there is no significant variation in teachers’ attitudes towards workload across schools. On the other hand, there is considerable variation in teachers’ time management practices across schools. Lastly, there is a moderate and positive significant correlation between teachers’ attitudes toward workload and time management practices. It is recommended that schools communicate effectively with teachers about workloads. Schools should ensure that the compensation is appropriate to the workload assigned. Schools are advised to provide opportunities for teachers' professional development. Also, schools should assess their leadership and organizational cultures to determine areas where improvement is needed. Schools should encourage teachers to reflect on their time management practices and offer them training and resources to enhance their skills. Lastly, future researchers should explore other variables affecting attitudes toward workload and time management practices, such as teacher support networks and work environments.